Pemanfaatan Metode Weighted Aggregated Sum Product Assesment Dalam Keputusan Pemilihan Personal Computer Untuk Kebutuhan Industri Game Developer - Sulistyawan, Perdana Eka Putra; Wibisono, Setyawan (Jurnal Mahajana Informasi, 2022)
With the advance of current technology, humanity is at ease to get their task done. Take example of a entertainment industry, the use of a computer is a vital point at developing a game. There is many considerable alternative of a personal computer that exist today. Some industry players that bought themselves a personal computer state that their device is just to much for supposed task and assume that it is best to spend the excess fund for another purpose, while the other complaints that their device is not achieving the expected result. WASPAS is an acronym for Weighted Aggregated Sum Product Assessment is one of many methods used for Multiple Criteria Decision Making which is widely known for it’s capability. Thus by designing system that  generate a decision result which is a personal computer for a game development purpose, for the industry player to get the precise target that they want.